2020
DOI: 10.1371/journal.pone.0235410
|View full text |Cite
|
Sign up to set email alerts
|

Improved patient satisfaction and diagnostic accuracy in skin diseases with a Visual Clinical Decision Support System—A feasibility study with general practitioners

Abstract: Patient satisfaction is an important indicator of health care quality, and it remains an important goal for optimal treatment outcomes to reduce the level of misdiagnoses and inappropriate or absent therapeutic actions. Digital support tools for differential diagnosis to assist clinicians in reaching the correct diagnosis may be helpful, but how the use of these affect patients is not clear. The primary objective of this feasibility study was to investigate patient experience and satisfaction in a primary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Isabel Health [ 21 ]: IsabelHealth is a commercial DDX generator built using machine learning technology [ 4 ]. It is a "black box" system for the user, where the thesauri used cannot be reviewed or improved by the tester.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isabel Health [ 21 ]: IsabelHealth is a commercial DDX generator built using machine learning technology [ 4 ]. It is a "black box" system for the user, where the thesauri used cannot be reviewed or improved by the tester.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical decision systems (CDSS) are increasingly used in practice [ 1 4 ]. However, all new methods in medicine, whether diagnostic or therapeutic, must be tested to demonstrate feasibility of use and benefit to patients.…”
Section: Introductionmentioning
confidence: 99%
“…In ve studies, clinicians provided a selfreport of time spent, using either a paper or electronic case report form. 87,93,94,101,106 A member of the research team manually timed the duration of study consultations or scenarios in four studies. 83,91,97,99 Five studies captured time data electronically from log les within the eCDS tool itself, including clinician time spent using particular elements of the tool or completing certain activities.…”
Section: Methods To Measure Consultation Durationmentioning
confidence: 99%
“…Twenty-four studies reported an objective of time. included: (i) time spent using or interacting with an eCDS tool (ranging from three seconds 83 to between 0.5-13 minutes [84][85][86][87][88][89][90][91] ) and/or (ii) consultation duration 83,[92][93][94][95][96][97][98][99][100][101][102][103][104][105][106] .…”
Section: Objectively-measured Impacts On Consultation Durationmentioning
confidence: 99%
“…This suggests a critical need for a CDSS to ameliorate current challenges within dermatology and other subspecialties in Botswana. Previous studies have demonstrated the promise of VisualDx CDSS as a platform which could contribute to increased provider con dence and a reduction in diagnostic errors in primary care settings [12,13].…”
Section: Introductionmentioning
confidence: 99%